Paixão por preservar: acervos de imagem em movimento da Escola de Belas Artes (UFMG), Museu da Imagem e do Som de Belo Horizonte e Arquivo Público Mineiro - Camila Cristina da Silva (2017)
This dissertation discusses the use of public policies and collection policies for the preservation and dissemination of moving images collections under the custody of three institutions: Escola de Belas Artes (EBA-UFMG), Museu da Imagem e do Som de Belo Horizonte (MISBH) and Arquivo Público Mineiro (APM). As there is still no National Policy on Audiovisual Heritage Preservation, this research focused on policies and measures adopted by public agencies in Brazilian, Minas Gerais and the city of Belo Horizonte horizons, in order to enable, even provisionally, the demands of these institutions. The objective of this research was to verify, through this methodology, the difficulties presented by the professionals who deal with these collections and to suggest improvements in the use of public policies and existing collections and, in the case of the Laboratório Memória e Cinema (EBA-UFMG), to suggest a policy of the colletion, which is one of the products of this dissertation.